Physical, chemical, mechanical, and thermal properties of charcoal briquettes produced from mangrove branch wood - Nuryawan, Arif; Simatupang, Jhonny; Risnasari, Iwan; Nur, Taufiq Bin; Fatriasari, Widya; Basyuni, Mohammad; Tambunan, Hardiansyah; Utami, Sentagi Sesotya; Jeong, Bora (Frontiers in Materials, 2025)
IntroductionCharcoal briquettes serve as a renewable energy source to reduce dependence on fossil fuels and meet global market demands.ObjectiveThe aim of this study was to evaluate the characteristics of charcoal briquettes made from the branches of three mangrove species and analyze the influence of the presence of bark and different species of mangrove wood branches on the properties of charcoal briquettes.MethodsCharcoal briquettes were manufactured from branches of three mangrove species: “bakau hitam” (Rhizophora mucronata), “tancang” (Bruguiera gymnorrhiza), and “mata buaya” (Bruguiera sexangula). The production process began with the conversion of branch wood (with and without bark), followed by carbonization using the pyrolysis method, grinding the charcoal into particle size, mixing with starch adhesive, and making charcoal briquettes with a size of 5 cm × 15 cm in a cylindrical shape.Results and DiscussionsThese results indicated that mangrove branch wood is highly suitable as a raw material for charcoal briquettes. The charcoal briquettes met the ISO/TS 17225-8:2016 TW1H standard, with values below 8% for moisture and above 5,016 cal/g for energy content. The results ranged from 0.00% to 6.46% and 6225–7,088 cal/g, respectively. Statistically, there were no significant differences in the properties observed among the charcoal briquettes, either based on the presence of bark (with and no bark) or the species of mangroves. These results demonstrated that mangrove woody branches could meet the industrial standard for making charcoal briquettes and that mangrove forest as the raw material source would be sustainable because only woody branches were utilized as bioenergy source.